Structural appraisal of a wrought iron truss railway bridge - Herath, S.R.; Abeyruwan, H.; Herath, K.R.B.; Dissanayake, U.I.; Gallage, D.J.; Vignarajah, M.; Raviprasad, M.; Ranaweera, M.P. (University of Jaffna, 2019)
A study for estimating load carrying capacity and remaining fatigue life of a wrought iron truss railway bridge is presented. The task is perused through static and dynamic field measurements and a numerical analysis. The dynamic factors obtained from the field testing were compared with those given by empirical formulae. For the numerical study, a three dimensional finite element model was prepared using SAP2000. Static responses obtained from the field load tests were used to validate the numerical model. A linear multi-step moving load case was introduced to the validated numerical model to determine member forces of the bridge under live loads. Based on the numerical solutions, along with dynamic and load factors for different type of engines and carriages, working stresses, factors of safety against yielding and fracture and remaining fatigue life were obtained and reported. The suitability of the bridge for anticipated increase of loading is verified. A bracing system for the bridge deck is suggested in order to reduce the lateral vibrations due to high speed trains.
Keywords: Wrought-iron railway bridge; Moving load; Dynamic factor; Vibration